A review on synergistic coexisting pollutants for efficient photocatalytic reaction in wastewater remediation - F. F.A., Aziz; Aishah, Abdul Jalil; Nurul Sahida, Hassan; Anees Ameera, Fauzi; M. S., Azami; N. W.C., Jusoh; Rohayu, Jusoh (Academic Press Inc., 2022)
With the tremendous development of the economy and industry, the pollution of water is becoming more serious due to the excessive chemical wastes that need to remove thru reduction or oxidation reactions. Simultaneous removal of dual pollutants via photocatalytic redox reaction has been tremendously explored in the last five years due to effective decontamination of pollutants compared to a single pollutants system. In a photocatalysis mechanism, the holes in the valence band can remarkably promote the oxidation of a pollutant. At the same time, photoexcited electrons are also consumed for the reduction reaction. The synergistic between the reduction and oxidation inhibits the recombination of electron-hole pairs extending their lifetime. In this review, the binary pollutants that selectively removed via photocatalysis reduction or oxidation are classified according to heavy metal-organic pollutant (HM/OP), heavy metal-heavy metal (HM/HM) and organic-organic pollutants (OP/OP). The intrinsic between the pollutants was explained in three different mechanisms including inhibition of electron-hole recombination, ligand to metal charge transfer and electrostatic attraction. Several strategies for the enhancement of this treatment method which are designation of catalysts, pH of mixed pollutants and addition of additive were discussed. This review offers a recent perspective on the development of photocatalysis system for industrial applications.